Penurunan Literasi Al‑Qur’an di Kalangan Mahasiswa Perguruan Tinggi Islam dan Implikasinya terhadap Pendidikan Islam Kontemporer perspektif Tafsir QS Al-‘Alaq Ayat 1–5: Studi Tahun 2022–2025 - Mukhrij Sidqy; Hafiz Taqwa; Sofyan Sauri; Muhammad Dzaky Hamid (Ikatan Dai Indonesia, 2025)
This study aims to examine the decline of Qur’anic literacy among students of Islamic Religious Higher Education Institutions (PTKI) in Indonesia during the period of 2022–2025, as well as to analyze the content of QS Al-‘Alaq verses 1–5 as a conceptual basis for the revitalization of Islamic education. Based on data from the Ministry of Religious Affairs in 2023, it was found that less than 35% of PTKI students are able to read the Qur’an correctly and fluently. This trend is concerning, given that the Qur’an is the primary source of knowledge and inspiration in Islamic education. The tafsir tahlili approach is used to comprehensively examine the meaning of the verses, while descriptive qualitative analysis is employed to relate the verses’ meanings to contemporary realities. The study’s findings show that these verses contain a strong message about the importance of reading, learning, and the intellectual transformation process based on revelation. This research recommends enhancing the Qur’anic literacy curriculum in PTKI and strengthening the role of lecturers as exemplars in practicing Qur’anic values.